Web-Based Online Sales Information System Using PHP and MYSQL Database in Nara Collection - Hendriyanto, Hendriyanto; Cakranegara, Pandu Adi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Online sales is an alternative form of business that can be used by business people to offer products to consumers. As internet service users continue to grow, due to being cheap and easy, business online sell is growing. Business development is supported by increased productivity which provides a variety of products to be marketed through the internet media. This has triggered the rise of ballet shoes selling business through the internet called "Nara Collection" because it is easy to run does not require large capital and does not need to require an easy management system to manage it. Now it is enough with the product photos and internet access to market it into goods selling sites and social networking sites, this business can already run. To simplify the online sales process, a web-based online sales information system was created. With this application, it can help market products online so that it can be widely known by the general public. In addition, the development of this information system makes the transaction process easier and faster and problems related to sales data and report information can be printed quickly and easily by the cashier.